Blood lactate and metabolic responses to controlled frequency breathing during graded swimming - West, S. A.; Drummond, M. J.; Vanness, J. M.; Ciccolella, M. E. (The Journal of Strength and Conditioning Research, 2005)
Controlled frequency breathing (CFB) is a training technique used by swimmers in an effort to simulate high-intensity workloads by limiting oxygen availability to the body and stimulating anaerobic metabolism. During CFB, a swimmer voluntarily restricts breathing, which, theoretically, limits oxygen availability and stimulates anaerobic metabolism. The purpose of this study was to determine the influence of CFB on blood lactate and metabolic responses during graded increases in swimming intensity. A free swimming (FS) protocol was used to determine blood lactate and heart rate (HR) responses to CFB, while a tethered swimming (TS) protocol was used to determine blood lactate, HR, and ventilatory responses to CFB. The subjects swam four 3-minute trials at workloads of 55, 65, 75, and 85% of peak intensity during both protocols. A total of 46 competitive collegiate swimmers participated in the study. Thirty-four subjects (14 men and 20 women) completed the FS protocol, and 12 subjects (7 men and 5 women) completed the TS protocol. CFB reduced ventilation and VO2 (p < 0.05) during the TS protocol and reduced HR (p < 0.05) during the FS protocol when compared to normal breathing. However, CFB did not alter blood lactate concentrations for either protocol (p > 0.05). Our findings demonstrate that although CFB does not alter the blood lactate response to graded increases in swimming intensity, it appears to reduce the ventilatory and HR responses to exercise. Thus, swim coaches can use CFB at moderate intensities to simulate high-intensity training but should consider adjusting HR training zones to reflect the reduction in HR associated with reduced ventilation.